Faktor-Faktor yang Berpengaruh Terhadap Minat Mahasiswa Untuk Mengikuti Pendidikan Profesi Akuntansi (PPAk) - Zazuk Sapitri; Rizal Yaya (Universitas Muhammadiyah Yogyakarta, Indonesia, 2015)
The purpose of this study is to determine factors that influence students’ interest in enrolling in the accounting professional education (PPAk). Some independent variables are hypothesised to have influence on the students interests. Sample of this study is 609 students majoring in accounting at semesters 6 and 8 at Universitas Muhammadiyah Yogyakarta (UMY). To answer research hypotheses, data were analysed by using multiple regression test. The result shows that variables of motivation for quality, motivation for gaining knowledge, education costs, and lenght of study have positive and significant effects on students’ educational interests in enrolling in PPAk. On the other hand, variables of career motivation, economic motivation, social motivation, title motivation, and motivation to take USAP exam do not have effect on students’ interest to take PPAk.